Glass slippers - Cypess, Leah (Cypess, Leah. Sisters ever after., 2022)
Everyone knows all about Cinderella and her wicked stepsisters, but most people forget about Cinderella's third younger stepsister, Tirza. Tirza was always kind to Cinderella, so she was given a home in the castle of Cinderella, now Queen Ella, instead of being banished like her sisters. But when Queen Ella's famous glass slippers go missing, Tirza becomes the number-one suspect. Tirza did try on the slippers, but she didn't steal them, and she sets out to clear her name and find the real thief. She soon discovers that her sisters may not have been as evil as Cinderella claims, and she wonders who she can really trust.